Cross‐species transmission and evolutionary dynamics of canine distemper virus during a spillover in African lions of Serengeti National Park. Issue 22 (15th May 2020) - Weckworth, Julie K.; Davis, Brian W.; Dubovi, Edward; Fountain‐Jones, Nicholas; Packer, Craig; Cleaveland, Sarah; Craft, Meggan E.; Eblate, Ernest; Schwartz, Michael; Mills, L. Scott; Roelke‐Parker, Melody
Abstract: The outcome of pathogen spillover from a reservoir to a novel host population can range from a "dead‐end" when there is no onward transmission in the recipient population, to epidemic spread and even establishment in new hosts. Understanding the evolutionary epidemiology of spillover events leading to discrete outcomes in novel hosts is key to predicting risk and can lead to a better understanding of the mechanisms of emergence. Here we use a Bayesian phylodynamic approach to examine cross‐species transmission and evolutionary dynamics during a canine distemper virus (CDV) spillover event causing clinical disease and population decline in an African lion population ( Panthera leo ) in the Serengeti Ecological Region between 1993 and 1994. Using 21 near‐complete viral genomes from four species we found that this large‐scale outbreak was likely  ignited by a single cross‐species spillover event from a canid reservoir to noncanid hosts <1 year before disease detection and explosive spread of CDV in lions. Cross‐species transmission from other noncanid species probably fuelled the high prevalence of CDV across spatially structured lion prides. Multiple lines of evidence suggest that spotted hyenas ( Crocuta crocuta ) could have acted as the proximate source of CDV exposure in lions. We report 13 nucleotide substitutions segregating CDV strains found in canids and noncanids. Our results are consistent with the hypothesis that virus evolution played a role in CDV emergence in noncanid hosts following spillover during the outbreak, suggest that host barriers to clinical infection can limit outcomes of CDV spillover in novel host species. Abstract : see also the Perspective by Pauline L. Kamath.